Ukrainian historical narrative in the period of Yushchenko's and Yanukovych's historical policy - Švec, Jiří (Civilia, 2014)
The emergence of independent Ukraine in 1991 launched the need to create a new conception of Ukrainian history. The basic features of this "nationalized" historical narrative is formed already in the first half of the 1990s. The fragile consensus in the field of Ukrainian historical memory did not last long and 2004 brought new controversies on sensitive issues of Ukrainian past. Historical policy of the last decade associated with President Yushchenko and Yanukovych is the central theme of the article, as well as a reflection of this policy in the official canon of Ukrainian history. Any modifications to the Ukrainian narrative will also be monitored on the basis of the analysis of new history textbooks.
Keywords: Yushchenko; Yanukovych; Ukraine; history; narrative